Wildlife of Florida Factsheet: Northern Crested Caracara - Elizabeth Rose; Raoul Keith Boughton (EDIS)
The Wildlife of Florida Factsheet series was created to provide the public with a quick and accurate introduction to Florida’s wildlife, including both native and invasive species. Authors Elizabeth Rose and Raoul Boughton hope this 2-page fact sheet published by the UF/IFAS Department of Wildlife Ecology and Conservation will inspire people to learn more about the northern crested caracara and understand the amazing biodiversity of wildlife in general in the state of Florida and in their own backyards and communities. http://edis.ifas.ufl.edu/uw452